Recapitulating idiopathic pulmonary fibrosis related alveolar epithelial dysfunction in a human iPSC‐derived air‐liquid interface model. Issue 6 (16th April 2020) - Schruf, Eva; Schroeder, Victoria; Le, Huy Q.; Schönberger, Tanja; Raedel, Dagmar; Stewart, Emily L.; Fundel‐Clemens, Katrin; Bluhmki, Teresa; Weigle, Sabine; Schuler, Michael; Thomas, Matthew J.; Heilker, Ralf; et al.
Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disease of unknown cause that is characterized by progressive fibrotic lung remodeling. An abnormal emergence of airway epithelial‐like cells within the alveolar compartments of the lung, herein termed bronchiolization, is often observed in IPF. However, the origin of this dysfunctional distal lung epithelium remains unknown due to a lack of suitable human model systems. In this study, we established a human induced pluripotent stem cell (iPSC)‐derived air‐liquid interface (ALI) model of alveolar epithelial type II (ATII)‐like cell differentiation that allows us to investigate alveolar epithelial progenitor cell differentiation in vitro. We treated this system with an IPF‐relevant cocktail (IPF‐RC) to mimic the pro‐fibrotic cytokine milieu present in IPF lungs. Stimulation with IPF‐RC during differentiation increases secretion of IPF biomarkers and RNA sequencing (RNA‐seq) of these cultures reveals significant overlap with human IPF patient data. IPF‐RC treatment further impairs ATII differentiation by driving a shift toward an airway epithelial‐like expression signature, providing evidence that a pro‐fibrotic cytokine environment can influence the proximo‐distal differentiation pattern of human lung epithelial cells. In conclusion, we show for the first time, the establishment of a human model system that recapitulates aspects of IPF‐associated bronchiolization of the lung epithelium in vitro .